NDIS Self‐Management Approaches: Opportunities for choice and control or an Uber‐style wild west?. Issue 4 (8th December 2017) - David, Christina; West, Raelene
Abstract: This article examines the emerging challenges and opportunities presented by self‐management options in Australia's National Disability Insurance Scheme (NDIS). We examine the three different ways in which NDIS participants can opt to self‐manage their funding and services, including direct employment and emerging Uber‐style online platforms, and explore the potential implications of these options for NDIS participants, service providers and the disability support workforce. In particular, we focus on these options in relation to the transition to a marketised services landscape being developed alongside the NDIS, and examine both the risks and opportunities for each stakeholder group. Through this analysis, we identify implications for policy and practice, in particular around regulatory mechanisms and the role of government within this emerging market economy and transforming service landscape.